2019
DOI: 10.1039/c9ra02230a
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA SMARCA5 inhibits gastric cancer progression through targeting the miR-346/ FBXL2 axis

Abstract: Circular RNA (circRNA) SMARCA5 (circSMARCA5) is a cancer-related circRNA that has been observed to be involved in the progression of several types of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 23 publications
(22 reference statements)
1
17
0
Order By: Relevance
“…Cai et al evaluated circSMARCA5 levels in 60 pairs of GC tissues and matched paracancerous tissues and the circSMARCA5 levels were remarkably reduced in cancer tissues compared to paired normal tissues ( Cai and Zuo, 2019 ). These findings were similar to those of Li et al ( Li and Hu, 2019 ) Similarly, the plasma circSMARCA5 expression level in GC patients was also reduced compared with that in healthy controls. Moreover, circSMARCA5 in plasma remained stable under some harsh conditions ( Cai and Zuo, 2019 ).…”
Section: Circsmarca5 and Tumorssupporting
confidence: 91%
See 3 more Smart Citations
“…Cai et al evaluated circSMARCA5 levels in 60 pairs of GC tissues and matched paracancerous tissues and the circSMARCA5 levels were remarkably reduced in cancer tissues compared to paired normal tissues ( Cai and Zuo, 2019 ). These findings were similar to those of Li et al ( Li and Hu, 2019 ) Similarly, the plasma circSMARCA5 expression level in GC patients was also reduced compared with that in healthy controls. Moreover, circSMARCA5 in plasma remained stable under some harsh conditions ( Cai and Zuo, 2019 ).…”
Section: Circsmarca5 and Tumorssupporting
confidence: 91%
“…Several studies have reported that circSMARCA5 levels in HCC tissues are lower than those in matched normal tissues ( Yu et al, 2018 ; Zhang et al, 2018 ; Li and Hu 2019 ). Moreover, the abundance of circSMARCA5 in plasma and tissues gradually decreases from healthy controls to hepatitis patients, cirrhosis patients and HCC patients, which indicates that circSMARCA5 expression is tissue-stage specific.…”
Section: Circsmarca5 and Tumorsmentioning
confidence: 99%
See 2 more Smart Citations
“…A large number of studies have demonstrated the role of circRNAs as miRNA-sponges in GC [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. For example, it has been shown that alterations in circLARP4/miR-424/LATS1 [ ...…”
Section: Introductionmentioning
confidence: 99%